Analisis kontribusi Superprof sebagai modernisasi pendidikan - Chasanah, Ajilni Diina Mar’atun Nur (Maliki Interdisciplinary Journal, 2024)
Human beings are creatures created by God by possessing intellect, then to develop the ability of intellect, a stimulus is needed which can help a person improve their thinking and intellectual power. Education consisting of learning and teaching elements is a stimulus created by man along with the alignment of fact and reality. Education according to Bloom’s taxonomy has 3 aspects, namely cognitive aspects, affective and psychomotor and it can all be connected in his med Learning. The more the world experiences globalization, the influence of progress Technology is also becoming more widespread. Not only in the field of science but also It has spread to the realm of humanities and even education. Technology brings The development is included in terms of learning media. This study discusses about one of the platforms in the internet, namely Superprof which provides contribution of Technology to education and Teaching Services as well as Information Services in the community in the realm of education. People who feel that they are unhappy to develop skills, you can find teachers through superprof without the need worried about the problem of geographical distance and the shortness of time. the purpose of the existence of this study is to find out how the superprof mechanism is providing information services and services through the website and how to its contribution to the modernization of education. In this study, the method of used is a qualitative descriptive analysis by making two studies as the basic benchmark. In addition, the collection technique and data on This research is as mentioned by Miles and Huberman (1992) namely using 3 data collection flows simultaneously, namely: reduction data, data presentation, and conclusion drawn. From the data that has been mentioned conclusions from the research were obtained, namely: Superprof as one of the products technology